UNEMPLOYMENT IN UKRAINE: CONTEMPORARY CHALLENGES - MOROZ, Sergiy (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the problem of unemployment in Ukraine. The essence of unemployment according to Ukrainian legislation has been defined. The theories of unemployment have been briefly described. Based on the statistical data of the State Employment Service, the number of unemployment and its dynamics in 2022 has been analyzed. The discrepancy between the actual number of unemployed and the registered number have been indicated. The number of unemployed has been analyzed in terms of types of economic activity. Based on the analysis of official data, a decrease in the number of unemployed in Ukraine has been noted.Analysis of the demand and supply of labor force have been conducted. With this aim the number of vacancies and the number of unemployed as of November 1, 2022 have been compared. The presence of a significant imbalance between the demand and the supply of labor force has been noted. Thus, it has been investigated that 7 officially registered unemployed are applying for one job.
Keywords: unemployment in Ukraine; employment; migration; labor migrants; labor supply and demand; theory of unemployment; vacancy; CV; market imbalance; excess supply of labor; salary